Effects of Indole Acetic Acid (IAA) and Indole Butyric Acid (IBA) to The Growth and Rooting of Ironwood (Eusideroxylon zwageri Teijsm. & Binn.) Air Layering - Bambang Irawan; Rike Puspitasari Tamin; Rizky Ayu Hardiyanti (Jurnal Manajemen Hutan Tropika, 2019)
Due to over exploitation, the population of Eusideroxylon zwageri is decreasing drastically. One simple technique to conserve the last remaining genetic resources of E. zwageri is by air layering. The experiment was divided into two. The experiment was conducted from July 2018 to February 2019. The first experiment was conducted using branches that grew from coppices while the second experiment using twigs that grew from normal adult trees. Randomized Block Design was applied with three replicates. The treatments were consisted of nine concentration of auxin namely 0 ppm of auxin; 1, 000 ppm; 1,500 ppm; 2,000 ppm and 2,500 ppm of IAA and 1,000 ppm; 2,000 ppm; 3,000 ppm and 4,000 ppm of IBA. The result of experiment shows that the IBA growth regulator seems to be more effective in regulating growth and rooting of E. zwageri air layering compared to IAA. Results for air layering which was taken from coppices revealed that 1,000 ppm of IBA obtained the best results. Air layering of branches taken from coppice is possible even without any additional growth regulator. While, air layering of twigs which was taken from normal trees revealed that the best treatment is 3,000 ppm of IBA.